Cytogenetic and Molecular Changes in Buccal Cells from Mechanical Workshop Workers - Eshkoor, Sima Ataollahi (2011)
Ageing results from the accumulation of mutations in the genome of somatic cells. The process leads to tissue atrophy, cellular alterations leading to neoplasia, and decreased functions of cells and tissue of the body. These effects of ageing appear to be due to the influences of both genetic and environmental factors, which affect the process at the cellular level. Ageing increases the risk of diseases, which eventually lead to death. In the susceptible population, ageing appears to be accelerated and therefore, risk of diseases might manifest at earlier age. Researchers continue to provide more information to support healthy life span in the susceptible people. In the study, it is hoped that through the investigation of the effects of occupational exposure on ageing, the possible genetic alteration associated with ageing could be identified, subsequently creating awareness for a better and meaningful life among the workers. The hypothesis was whether the occupational and environmental exposures were associated with genotoxic effects in the mechanical workshop workers, which speeds up the ageing process. The investigation was carried out using different methods to determine the cytogenetic and molecular changes in the worke and control group. Exfoliated buccal cells were obtained from 120 exposed and 120 non-exposed individuals by scraping the oral cavity using a cytology brush. Subjects were interviewed on their work history and duration of working time, state of health, smoking habit, alcohol consumption and other aspects relevant to the study. The methods employed in the study included micronuclei (MN) test, comet assay, real-time PCR, multiplex PCR, and restriction fragment length polymorphism (RFLP) analyses. The methods assessed cytogenetic and molecular changes related to the ageing process. This project indicated that the occupational exposure could enhance the speed of ageing based on the biological markers alterations. This investigation showed statistically significant effects (p<0.05) of the occupational exposure on the biomarkers namely, MN, comet tail length and telomere length through comparing the workers and controls. In this study, molecular analysis revealed the possible effects of selected genes on the biomarkers. In the study, gene polymorphisms of Glutathione-S-transferases (GSTs) and Cytochrome P450 (CYP450) enzymes were assessed in the exposed and non-exposed population. Statistical analysis using the Mann-Whitney test and independent t-test showed significant differences (p<0.05) in MN, comet tail length and relative telomere length between the workers and controls. A statistically significant correlation (p<0.05) was found between each biomarker and age. GSTM1 polymorphism showed statistically significant effects on MN frequency (p=0.001), comet tail length (p=0.009) and relative telomere length (p=0.025). GSTT1 polymorphism did not show any statistically significant effects (p>0.05) on any of the three biomarkers at the occupational exposure. GSTM1 represented significant effect on MN in the groups of younger (<30 years old) and all ages in the controls (p<0.05). GSTT1 did not show any significant effects (p>0.05) on the biomarkers in each group of age in both the workers and controls. GSTP1 and Cytochrome P4501A1 (CYP1A1) genes did not show any statistically significant effects (p>0.05) on all three biomarkers in the different age groups as well. Cytochrome P4501A2 (CYP1A2) did not show any statistically significant effects (p>0.05) on the biomarkers in the age groups in the workers and controls except significant effect on comet tail length (p=0.047) in the younger group of workers. Cytochrome P4502E1 (CYP2E1) showed statistically significant effects on MN (p=0.007) and relative telomere length (p=0.047) in the older group of workers and MN in the younger group of controls (p=0.020). It indicated that the CYP450 and GSTP1 enzymes probably protected the genomic material of cells against ageing damages except CYP2E1 polymorphism, which contributed in acceleration of ageing. The results showed differences in significance of effects of genes on the biomarkers. These differences can be attributed to gene polymorphisms and their interactions. It appeared that the socio-demographic factors contributed to the genetic damage, which could result in synergistic or additive effects on ageing. In conclusion, the cellular and molecular analysis indicated that hazards in the environmental and occupational exposure contributed to genotoxic and cytotoxic damages within cells, could cause the accelerated ageing. Overall, it seemed that MN is more sensitive than the other biomarkers to reflect genetic damages. However, there are problems in getting good results as well as their interpretations due to insufficient sample size in each group of ages and genotypes. The socio-demographic factors also seemed as confounding factors that could interfere with the results. Further studies with enough sample size for each group of all variables are needed to clarify the role of each biomarker. These assessments could be used to screen the vulnerable individuals and better protect them.